2020
DOI: 10.3390/joitmc6040187
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Technologies and Related Urban Planning and Development Concepts: How Are They Perceived and Utilized in Australia?

Abstract: Artificial intelligence (AI) is a powerful technology with an increasing popularity and applications in areas ranging from marketing to banking and finance, from agriculture to healthcare and security, from space exploration to robotics and transport, and from chatbots to artificial creativity and manufacturing. Although many of these areas closely relate to the urban context, there is limited understanding of the trending AI technologies and their application areas—or concepts—in the urban planning and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…The upcoming digital urban infrastructure that will be supporting future societies will intrinsically be based on AI [118]. This is evident from the work on the sixth-generation (6G) networks with extreme-scale ubiquitous AI services through the next-generation softwarization, platformization, heterogeneity and configurability of networks [119][120][121].…”
Section: Responsible Local Government Artificial Intelligencementioning
confidence: 99%
“…The upcoming digital urban infrastructure that will be supporting future societies will intrinsically be based on AI [118]. This is evident from the work on the sixth-generation (6G) networks with extreme-scale ubiquitous AI services through the next-generation softwarization, platformization, heterogeneity and configurability of networks [119][120][121].…”
Section: Responsible Local Government Artificial Intelligencementioning
confidence: 99%
“…Transportation is no exception where social media has been used to study various aspects such as for analysing travel behaviours [15], recognizing mobility patterns [16], congestion detection [17], and event detection [4,6,9,18,19]. Due to the microblogging and real-time nature of Twitter, people are likely to communicate information about small and large-scale social gatherings, sports events, or events such as a fire, weather, allowing such information to be extracted in real-time [20]. Such information can allow the detection of transportationrelated events and their causes for timely planning and operations.…”
mentioning
confidence: 99%
“…It is often difficult to obtain consistent results and the required quality of the image with each test image due to several interferences and limitations of this technique. It is often observed that pre-defined algorithms or scripts may work fine for a certain set of images while it may not be able to process other sets of images due to inconsistencies that may be due to various factors [82,83]. To address these issues, various AI and machine learning tools can be adopted.…”
Section: Discussionmentioning
confidence: 99%